2011
DOI: 10.1007/s12562-011-0322-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of taurine deficiency in inducing green liver symptom and effect of dietary taurine supplementation in improving growth in juvenile red sea bream Pagrus major fed non-fishmeal diets based on soy protein concentrate

Abstract: This study was conducted to investigate the mechanism of green liver symptom induction and the effect of dietary taurine supplementation on growth performance in juvenile red sea bream fed non-fishmeal diets based on soy protein concentrate (SPC). Juvenile fish (initial BW 72 g) were fed for 20 weeks on SPC diets supplemented with taurine at levels of 0, 1.0, and 2.0%. In the taurineunsupplemented SPC diet group, specific growth rate (SGR) and feed conversion ratio (FCR) were significantly inferior (P \ 0.001)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 42 publications
6
40
1
1
Order By: Relevance
“…However in red seabream Pagrus major, no difference in hematocrit was observed despite the presence of green liver syndrome, a characteristic symptom of taurine deficiency in this species (Goto et al, 2001). Takagi et al (2011) observed no difference in hematocrit in red seabream either, although there was a lower erythrocyte count in fish fed low taurine diets. In the present study we did not observe a significant decrease in PCV or an increase in serum bilirubin over time (Tables 2 and 3), suggesting hemolysis had not occurred under these conditions.…”
Section: Taurine and Osmoregulationmentioning
confidence: 69%
See 1 more Smart Citation
“…However in red seabream Pagrus major, no difference in hematocrit was observed despite the presence of green liver syndrome, a characteristic symptom of taurine deficiency in this species (Goto et al, 2001). Takagi et al (2011) observed no difference in hematocrit in red seabream either, although there was a lower erythrocyte count in fish fed low taurine diets. In the present study we did not observe a significant decrease in PCV or an increase in serum bilirubin over time (Tables 2 and 3), suggesting hemolysis had not occurred under these conditions.…”
Section: Taurine and Osmoregulationmentioning
confidence: 69%
“…However, this is not conserved in all species: in juvenile Atlantic salmon Salmo salar kept in seawater and fed plant-based diets, there was an increase in hepatic taurine in response to methionine supplementation, suggesting an increased activity in the transsulfuration pathway (Espe et al, 2008). Perhaps the best-recognized symptom of taurine deficiency in fish is the green-liver syndrome caused by an overproduction of bile pigments biliverdin and bilirubin (Takagi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Taurine may be synthesized endogenously from methionine, but this capacity depends on fish species (El‐Sayed, ; Salze & Davis, ); nevertheless, it has been suggested that taurine supplementation augments trout growth only when dietary methionine level is suboptimal (Gaylord et al., ), meaning that this species is efficiently able to convert methionine to taurine. But this is not the case of Rachycentron canadum , Pagrus major , Scophthalmus maximus and Paralichthys olivaceus that the fish showed reduced growth performance when fed with diets containing optimal methionine but suboptimal taurine (Kim et al., ; Lunger et al., ; Qi et al., ; Takagi et al., ). Dietary methionine requirement has not been determined in many sturgeon species including Persian sturgeon; however, dietary methionine levels in treatments M and MT were similar to Acipenser transmontanus requirement (Ng & Hung, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, soybean meal is deficient in methionine and particularly taurine, two sulphur‐containing amino acids. Generally, soybean‐based fish feeds are supplemented with methionine, to support optimum fish growth (Boonyoung, Haga, & Satoh, ; Espe, HevrĂžy, Liaset, Lemme, & El‐Mowafi, ; Mambrini, Roem, Carvedi, Lalles, & Kaushik, ), but taurine supplementation to plant‐based feeds gained attention recently (Gaylord, Teague, & Barrows, ; Jirsa, Davis, Salze, Rhodes, & Drawbridge, ; Johnson et al., ; LĂłpez, Flores‐Ibarra, Bañuelos‐Vargas, Galaviz, & True, ; Lunger, McLean, Gaylord, Kuhn, & Craig, ; Takagi et al., ; Wu, Han, Qin, & Wang, ). Taurine (2‐aminoethanesulphonic acid) is an amino acid, which does not participate in protein structure and is generated as final product of sulphur‐containing amino acids metabolism (Salze & Davis, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is quite necessary to supplement exogenous taurine in feeds of marine carnivorous fish. Recently, many studies have shown that the taurine supplementation in diets could alleviate the negative effects of high level of plant proteins (Bañuelos‐Vargas, LĂłpez, PĂ©rez‐JimĂ©nez, & Peres, ; Boonyoung, Haga, & Satoh, ; Chatzifotis, Polemitou, Divanach, & Antonopoulou, ; Jirsa, Davis, Salze, Rhodes, & Drawbridge, ; Jirsa, Stuart, et al., ; Takagi et al., , , ; Takagi, Murata, Goto, Hayashi, et al., ; Takagi, Murata, Goto, Ichiki, et al., ; Yun et al., ). Takagi et al.…”
Section: Introductionmentioning
confidence: 99%